Epidemiology of mental disorders during pregnancy and link to birth outcome: a large-scale retrospective observational database study including 38,000 pregnancies - Wallwiener, Stephanie; Götz, Maren; Gillessen, Andrea; Feißt, Manuel; Sohn, Christof; Wallwiener, Markus (Archives of gynecology and obstetrics, 2019)
PurposeTo investigate the real-life epidemiology of mental disorders during pregnancy and their impact on birth outcome in an unselected low-risk population in Germany.MethodsClaims data of the Techniker Krankenkasse (TK) were analyzed as part of a retrospective observational study over a one-year period from 01/2008 to 12/2008 including 38,174 pregnant women. ICD-10 codes were clustered into four diagnostic groups: depression, anxiety disorders, somatoform/dissociative disorders and acute stress reactions. The relationship between mental disorders, birth mode and infant weight was tested using chi-squared tests and multivariate logistic regression. Main outcome measures included the prevalence of mental disorders during pregnancy, performed cesarean sections and infants born underweight.ResultsN = 16,639 cases with at least one diagnosis from the four mental disorder diagnostic groups were identified: 9.3% cases of depression, 16.9% cases with an anxiety disorder, 24.2% cases with a somatoform/dissociative disorder, and 11.7% cases of acute stress reactions. Women diagnosed with a mental disorder were more likely to deliver their child by cesarean section ([depression: OR =1.26 (95% CI 1.14-1.39); anxiety: OR 1.11 (95% CI 1.02-1.19); somatoform disorders: OR 1.12 (95% CI 1.05-1.20); acute stress reactions: OR 1.17 (95% CI 1.07-1.28)]. Furthermore, infants of women diagnosed with an ICD-10 code for depression during pregnancy were more likely to be underweight and/or delivered preterm [OR =1.34 (95% CI 1.06-1.69)].ConclusionsWe observed substantially high prevalence rates of mental disorders during pregnancy which urgently warrant more awareness for validated screening and adequate treatment options.